Heterogeneity of failure of visual acuity in Graves' disease. Issue 642 (April 1979) - Sachdev, Y.; Chatterji, J. C.; Sharma, R. C.
Abstract : The eye manifestations of Graves' disease are usually mild and self-limiting. Occasionally they follow a progressive course leading to visual loss and total blindness. The ocular manifestations bear no relationship to the metabolic state and may appear before, during or after onset of thyrotoxicosis. Characteristically they become evident at about the time of onset of hypermetabolism. Various factors responsible for the failure of visual acuity are discussed with case illustrations.